2018
DOI: 10.5539/ijbm.v13n5p1
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Reporting Practices in Europe and Value Relevance of Accounting Information under the Framework of IIRC

Abstract: The research has been conducted on a sample of European companies with the aim to investigate whether the adoption of the Integrated Reporting (IR) affects the value relevance of summary accounting information. The relations between Market Value (MV) and traditional accounting information (Book Value and Earnings) are studied by a linear price-level model, typical of the studies on the value relevance of accounting information. The results of analysis show that the degree of value relevance of Earnings is sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Moreover, in a highly risky and uncertain market, investors are driven to have the tools to control the cost of equity to invest it in a favourable and certain climate. Our result is, therefore, consistent with those of Salvatore et al (2018) and Wahl et al (2020).…”
Section: Regression Analysissupporting
confidence: 93%
“…Moreover, in a highly risky and uncertain market, investors are driven to have the tools to control the cost of equity to invest it in a favourable and certain climate. Our result is, therefore, consistent with those of Salvatore et al (2018) and Wahl et al (2020).…”
Section: Regression Analysissupporting
confidence: 93%
“…Also, studies such as Loprevite et al (2018) confirm the IIRC's assessment that the integrated report is expected to improve the quality of traditional accounting information for financial capital providers. Therefore, when analyzing the value relevance of the integrated reports of companies in Europe, they found that the degree of relevance of the profit value is significantly different for companies that publish IR compared to companies that adopt only the traditional financial report.…”
Section: Literature Review 21 Integrated Reporting In Brazilmentioning
confidence: 80%
“…They found that studies made in a predominantly North American context or a European context similar to the North American (such as the United Kingdom) demonstrate the value relevance of voluntary non-financial disclosure (Berthelot et al, 2012;Chapple et al, 2013;Hussainey & Salama, 2010;Johnston et al, 2008;Lourenço, Branco, Curto, & Eugenio, 2012;Sinkin et al, 2008). On the contrary, studies conducted in the Continental European context show mixed results, with only a few studies finding that non-financial information is value relevant (Reverte, 2016;Schadewitz & Niskala, 2010), whereas other studies do not corroborate such findings (Carnevale et al, 2012;Cormier & Magnan, 2007;Moneva & Cuellar, 2009 (Cortesi & Vena, 2019) and an increase in the value relevance of earnings (Baboukardos & Rimmel, 2016;Loprevite, Rupo, & Ricca, 2018).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 96%
“…To our knowledge, the effects of such adoption on the value relevance of non‐financial disclosure have not been investigated yet, with the exception of Veltri, De Luca and Phan (2020) that focuses on the value relevance of risk disclosure in the post‐adoption period. Many recent studies have investigated the value relevance of the mandatory adoption of the Integrated Reporting (IR) framework (IIRC, 2013) in South Africa, showing that the adoption of IR is associated with a reduction of information asymmetries (Cortesi & Vena, 2019) and an increase in the value relevance of earnings (Baboukardos & Rimmel, 2016; Loprevite, Rupo, & Ricca, 2018).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%